Impact of The Covid-19 Pandemic on The Financial Performance of Regional Public Companies (Study on Tirta Hita Buleleng District Public Drinking Water Supply Company) (International Conference of Graduate School on Sustainability (ICGSS), 2021)
Tirta Hita Buleleng District Public Drinking Water Supply Company was established to provide clean water for people in Buleleng Regency. As a regional company, apart from being able to provide drinking water that meets the requirements of quality, quantity, and continuity, it also expected to contribute to increasing local revenue. The Covid-19 pandemic had major impact on the economic and social sectors, including the weakening of people's purchasing power and investment, which has implications for people's low incomes. For this company, Covid-19 caused problems to increase the number of customer arrears by 2000 households, as well as a decrease in income by 1 billion rupiah. This study aims to determine the impact of Covid-19 on financial performance of Tirta Hita Buleleng District Public Drinking Water Supply Company. Financial performance were measured by: current ratio, total assets turn over, return on equity, debt to equity ratio, earnings per share. The reporting period was Financial Statements for 2019 (before Covid-19) and 2020 (after Covid-19). The population in this study were all branch of Tirta Hita Buleleng District Public Drinking Water Supply Company covering the head office and 9 branch offices. The sample selection in this study used a non-probability sampling technique, with a purposive sampling approach. The data used are primary and secondary data. The tests carried out were descriptive statistical tests, normality tests, and Wilcoxon signed rank tests. Data analysis to test the hypothesis was a paired different sample test. The results showed that there were significant differences in total assets turnover, return on equity, earnings per share, current ratio, debt to equity ratio.